The Impact of Using Mathematical Models in the Growth of Regional Economic Indicators, Strengthening the Role of the State (European Journal of Marketing and Economics, 2018)
The purpose of this paper is the identification of the relationship between exchange rate and inflation directly and indirectly having their factors in the stability and development of the economy. The term "public policy" is not recent. It was introduced in the language of European political and administrative sciences in the 1970’s as a literal translation of the term "public policy".Based on the society's viewpoint and its policy and policy relations, politics can be divided into three branches, which according to Anglo-Saxon terminology are called politics, policy and polity.The findings and analysis, conclusions and recommendations which will be part of important scientific studies in this paper that will serve to assist in the preservation of natural resources in our countries. Politics (polity) means consensus by the electoral body for political power and the inter-social cohesion of different groups and strata. Three aspects intertwine and influence each other by implementing complex socio-political dynamics. Another purpose is the direct impact analysis that has the exchange rate of micro economy development, macro economic factors such as economic growth, and the impact of GDP growth, inflation and employment levels. By politics it is meant the activities of various political parties or different groups to enable the possessing and having the political power. By policy are meant the laws or other legal acts implemented by the political power to manage public property.
Keywords: Math models, exchange rate, empirical studies, management public politics, state